PEMIKIRAN NURCHOLISH MADJID TENTANG PLURALISME AGAMA DALAM KONTEKS KEINDONESIAAN - Johan Setiawan (IAIN Kendari, 2019)
This article talked about Nurcholis Madjid’s thoughts about religion pluralism in Indonesian context. This research was a library research where library resource and other literatures became the main data source. This research results showed that there were three thoughts of Nurcholis Madjid about religion pluralism, such as: First, according to him, religion pluralism was a view that acknowledge other religions’ differences and behave maturely towards diversity. Second, religion pluralism idea of Nurcholis Madjid was a religious principal that acknowledge religious freedom, live with the risk that will be held by each of religious person. Third, according to Nurcholish Madjid, religion pluralism in Islam was not based on doctrine assuming that all religions are right, but Islam merely acknowledge each religion to exist with freedom of running each religion so that tolerance in life can be formed in Indonesian.